Pain ………is not a lifestyle, pain is inevitable, suffering is optional - Kalthum Hashim (2015)
Animals were perceived that they do not feel pain. As time goes by and as human is more sensitive to animal feeling, we realised that animals do experience pain. Studies have shown that all mammals have similar neural pathways and neurotransmitters required for the transmission and perception of pain. Furthermore ethical consideration towards pain management in animals triggered numerous research interests in this area. Analgesia is the study of pain perception. ‘An’ is no and ‘algesia’ is feel. Pain is define as an aversive sensory and emotional experience representing awareness by the animal of damage or threat to the integrity of its tissues.